PCR-Based Detection of Priority Bacterial Biological Threat Agents: Advances in Diagnosis of Anthrax, Tularemia and Brucellosis - A. P. Gerilovych; N. O. Shevchenko; H. Ye. Anan’ina; E. O. Nardid; L. V. Stepanyuk; A. M. Sergienko; V. P. Martsenyuk (One Health Journal, 2026)
The rapid and accurate detection of high-consequence bacterial pathogens is essential for public health preparedness, veterinary medicine, food safety, and biodefense. Within the One Health framework, molecular diagnostics have become indispensable for integrated surveillance of zoonotic diseases affecting humans, animals, and the environment. This review summarizes current advances in polymerase chain reaction (PCR)-based detection of three priority bacterial biological threat agents: Bacillus anthracis, Francisella tularensis, and Brucella spp. The diagnostic principles, major genetic targets, specimen selection, and performance characteristics of conventional PCR, real-time quantitative PCR (qPCR), multiplex PCR, nested PCR, digital PCR (dPCR), and loop-mediated isothermal amplification (LAMP) are discussed. Particular attention is given to the role of multiplex molecular assays in the simultaneous detection and differentiation of biological threat agents, improving diagnostic speed, sensitivity, and laboratory biosafety. The review also highlights the expanding application of PCR technologies in biosurveillance, environmental monitoring, wildlife and vector surveillance, outbreak investigations, and laboratory preparedness for biological emergencies. Emerging innovations, including portable point-of-care PCR platforms, CRISPR-based diagnostics, whole-genome sequencing integration, artificial intelligence-assisted data interpretation, and cloud-based surveillance systems, are evaluated as future components of comprehensive biodefense strategies. Collectively, these technologies strengthen coordinated One Health surveillance by enabling rapid pathogen detection, improved epidemiological investigations, and timely response to naturally occurring outbreaks as well as deliberate biological threats, supporting global health security and modern laboratory preparedness.